Impact of lorcaserin on glycemic control in overweight and obese patients with type 2 diabetes: analysis of week 52 responders and nonresponders. Issue 6 (17th August 2016) - Pi-Sunyer, Xavier; Shanahan, William; Fain, Randi; Ma, Tony; Garvey, W. Timothy
ABSTRACT: Objectives : Treatment guidelines for type 2 diabetes mellitus (T2DM) suggest weight loss as a means to maintain glycemic control. Lorcaserin has been approved for chronic weight management in the United States as an adjunct to a reduced-calorie diet and exercise, and the previous phase 3 Behavioral Modification and Lorcaserin for Obesity and Overweight Management in Diabetes Mellitus (BLOOM-DM) study has shown that, in addition to weight loss, lorcaserin is associated with improvements in glycemic parameters. In this post hoc analysis of the BLOOM-DM trial, the relationship between responder status (patients achieving ≥5% weight loss at Week 52) and glycemic and cardiometabolic parameters is evaluated. Methods : Data are presented for patients receiving lorcaserin 10 mg twice daily or placebo for 52 weeks. Results : More than twice as many patients receiving lorcaserin plus diet and exercise counseling were classified as Week 52 responders compared to those receiving diet and exercise counseling alone (37.5% vs. 16.1%, respectively; p  < 0.001), and lorcaserin Week 52 responders had greater improvements vs. placebo Week 52 responders in FPG (−38.1 mg/dL vs. −26.0 mg/dL) and HbA1c (−1.3% vs. −1.0%). Furthermore, more lorcaserin-treated Week 52 responders decreased the number of concomitant oral antidiabetic medications (OADs) used, and fewer increased the number of OADs used, compared to placebo. Unexpectedly, lorcaserin Week 52 nonresponders also had substantial reductions in glycemic levels, despite very modest weight loss. Conclusions : These data support lorcaserin use in overweight and obese patients with T2DM to promote weight loss and facilitate glycemic control. Clinical trial registration :www.clinicaltrials.gov identifier is NCT00603291